The impact of digitalization on organizational agility: evidence from the enterprise survey for innovation and entrepreneurship in China - Jingyi Zhang; Sha Zhang; Xiongkai Tan; Hong Zhao (Humanities & Social Sciences Communications)
Abstract From public health emergencies to unpredictable geopolitical patterns to increasingly severe climate disasters, the constant evolution of these external factors makes business development full of uncertainty. Sudden public events such as COVID-19 have deeply influenced the global economy, posing enormous challenges and crises to many firms. Managing crises and boosting agility and survival chances has become a significant area of research amid complex market. This study is conducted against this backdrop, aiming to thoroughly investigate the influence of digitalization on organizational agility. Using a multiple linear regression model, it examines the influence of digitalization on agility based on data from ESIEC. Additionally, endogeneity and robustness checks are performed to verify the results. The findings indicate that firms that digitalization exhibit greater agility when confronted with crises, enabling them to promptly adapt their business models to address issues. Meanwhile, the number of participating platforms and the firm’s industry competitiveness negatively moderate this effect. This study is an innovative effort to link the existing research on digitalization with the literature on organizational agility. It offers valuable insights and practical guidance on how to improve organizational agility.